Improvement of power efficiency of hybrid white OLEDs based on p-i-n structures - Apisit Chittawanij; Kitsakorn Locharoenrat (My University, 2018)
In this article, hybrid white organic light-emitting diodes (WOLEDs) under p-i-n structures have been investigated in terms of power efficiency. By using tris(8-hydroxy quinolinato) aluminum (Alq3) doped with 8-hydroxy-quinolinato lithium (Liq) as an n-type and WHI112 doped with molybdenum trioxide (MoO3) as a p-type, the typical device structure of ITO/WHI112: 20 wt.% MoO3 (55 nm)/HTG-1 (10 nm)/UBH15: 3 wt.% EB502 (10 nm)/EPH31: 3 wt.% EPY01 (25nm)/3TPYMB (10 nm)/Alq3: 33 wt.% Liq (25 nm)/Al (150 nm) was fabricated. It has been found that the p-i-n device based device showed the lowest driving voltage and highest power efficiency among the undoped and n-type devices. At the current density of 20 mA/cm2, the roll-off of the efficiency in the p-i-n device was much smaller than the n-type and the undoped devices. The current and power efficiency of the p-i-n device were maintained with 17.2 cd/A and 5.1 lm/W at 100 mA/cm2, it was reduced to 7.5 % and 21 %, respectively. In contrast, the n-type device exhibited the significant reduction of efficiency (14.4 cd/A and 3.8 lm/W at 80 mA/cm2), it was reduced to 20 % and 39.6 %, respectively. The superior performances of the p-i-n structure based device were attributed to the high hole injection ability of WHI112:MoO3 and high electron mobility of Alq3:Liq, leading to high power efficiency and low driving voltage. A better balance of electrons and holes could contribute to a good current efficiency for the device. These findings strongly indicated that carrier injection ability and balance showed significant affects on the performance of OLED.
Keywords: Molybdenum trioxide; Organic Light-Emitting Diodes Research